Adoption of The Utaut3 Model by Mobile Banking Users of Bank Syariah Indonesia - Salsabila Putri Widyadana; Setiawati, Erma; Rina Trisnawati (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study examines the adoption of mobile banking using the UTAUT3 model among Bank Syariah Indonesia customers, particularly millennials in Semarang, Pekalongan, and Solo, Central Java. Employing a quantitative approach, data were collected via Google Forms questionnaires from a purposive sample of 300 respondents. Variables studied include Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit, Personal Innovativeness, Behavioral Intention, and Use Behavior. Data were analyzed using SmartPLS SEM to test the relationships among constructs. Results indicate that Performance Expectancy, Effort Expectancy, Facilitating Conditions, Price Value, Habit, Personal Innovativeness, and Behavioral Intention significantly influence Behavioral Intention and Use Behavior. Conversely, Social Influence and Hedonic Motivation do not significantly affect Behavioral Intention. These findings suggest that millennials’ mobile banking adoption is driven primarily by perceived usefulness, ease of use, supportive conditions, value, habits, and personal innovativeness, while social pressure and hedonic factors play a minor role.